Economic systems in developing countries: A macro cluster approach - Markus Ahlborn; Rainer Schweickert (Kiel Institute for the World Economy (IfW), 2017)
The literature on economic systems and corresponding empirical studies have largely focused on a classification for developed countries, while other world regions have only partly been included and/or not compared to established OECD prototypes on an income-adjusted basis. In our macro clustering approach, we apply Ward as well as Fuzzy C-Means clustering methods and, in contrast with other approaches, correct for the income bias in clustering variables. We are therefore able to include a worldwide sample of 115 developed and developing countries, the latter including transition countries. The major result from using income adjusted variables is that developing countries phase into the OECD divide. On the one hand, most African and Latin American countries join the liberal OECD prototype economies in the world of inequality. On the other hand, a large part of Asian developing countries as well all transition countries join the coordinated and liberal European market economies in the world of equality. As a robust result, European Nordic and transition countries form a cluster combining high levels of innovation and equality if income differences are phased out. At the same time, as argued by La Porta et al. (2008) and Lange et al. (2006), the distribution of non-transition developing countries between and within these worlds of equality and inequality reveals a clear distinction between British vs. other colonial heritages as one driver of economic systems today.
Keywords: H10; P10; P51; 330; Economic Systems; Varieties of Capitalism; Worlds of Welfare States; Cluster Analysis; Principal Components Analysis; OECD; Developing Countries